Government Information Policy in the Era of Big Data. - Washington, Anne L. (Review of Policy Research, 2014)
Reliable public sector information serves as a pivotal source for big data. Government postal codes, for instance, have been crucial for predicting demographics. Confidentiality, however, may be at risk when combined with other sources. Public sector information not only describes government activity but contains material, such as campaign finance filings, produced by outside sources. How does information production impact policy concerns if material is reused for big data projects? Information production is analyzed using a framework of five methods of production. The framework considers information that the public sector writes, publishes, manages, produces through research, and compiles through legal mandates. This paper examines the policy implications of using U.S. federal public sector information in big data projects.